Impacts of policies on market formation and competitiveness: The case of the PV industry in Germany - Barbara Breitschopf (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
This paper analyzes the impact of German policies promoting PV on industry structures and technological changes in the PV sector. A quantitative analysis is conducted by applying a set of policy variables derived from demand-, supplierand R&D-focused policies. To depict the industry structure, the production volume in MW of German PV module and cell manufacturers offers a good basis to derive structural variables. Patent applications are used to illustrate technological changes and competitiveness. The approach includes a descriptive as well as a multivariate analysis relying on the operationalization of demand policies and a policy mix. The results underpin the significance of demand policies and a policy mix for market formation and knowledge generation. But they also indicate that policies enhancing PV demand induce growth in PV industries abroad as well, which in turn affects domestic industry structures.
urn:nbn:de:0011-n-3566373
Keywords: 330; photovoltaic industry; renewable energy; patents; technological change; competitiveness; Germany